Prevalence Of Cryptosporidiosis In Buffaloes In And Around Bhubaneswar, Odisha - Mohanty, B.N.; Panda , M.R. (Indian Journal of Veterinary Sciences and Biotechnology, 2012)
Faecal samples collected from 305 buffaloes (89 diarrheic and 216 non diarrheic) of different age and sex from Bhubaneswar and adjacent areas of Cuttack and Puri district were examined during a period of three years. Cryptosporidial oocysts were detected in 76 (24.92%) faecal samples . Prevalence of cryptosporidiosis was higher in diarrheic than non diarrheic buffaloes. Significant variation was observed in prevalence between diarrheic and non-diarrheic buffaloes (P
Keywords: Prevalence; Cryptosporidiosis; Buffaloes